Living with Atopic Dermatitis as a Young Adult in Relation to Health-related Quality of Life and Healthcare Contacts: A Population-based Study - Susanne Lundin; Anna Bergström; Carl-Fredrik Wahlgren; Emma K. Johansson; Niklas Andersson; Natalia Ballardini; Marina Jonsson; Erik Melén; Inger Kull (Medical Journals Sweden, 2022)
Most studies of health-related quality of life (HRQoL) and atopic dermatitis are based on data from dermatology clinics. The aim of this study was to determine whether atopic dermatitis affects HRQoL in adolescence and young adulthood, based on data from the population-based cohort BAMSE (Children, Allergy, Environmental, Stockholm, Epidemiology). A further aim was to determine if the use of topical corticosteroids and healthcare contacts affect HRQoL. Participants with data from birth to young adulthood (n=3,064) were included. Two generic instruments were used to measure HRQoL:General Health at age 12, 16 and 24 years and EQ-5D-3L, including EQ-visual analogue scale (EQ-VAS) at age 24 years. In addition, the disease-specific Dermatology Quality Life Index (DLQI) was used at 24 years. Healthcare consultations for atopic dermatitis were obtained from Stockholm Regional Healthcare Data Warehouse (n = 1,944). Participants with atopic dermatitis had an increased odds ratio (OR) of not feeling completely healthy (adjusted OR 1.50; 95% confidence interval (95% CI): 1.30-1.73). Participants with persistent atopic dermatitis, fulfilling atopic dermatitis criteria in the 12- and/or 16- and 24-year follow-ups reported worse EQ-VAS value 70.0 (95% CI 67.3-72.7) in the 25th percentile, than peers without atopic dermatitis. Over an 8-year period, contact with healthcare was limited (mean number 0.96). In conclusion, atopic dermatitis had a negative impact on HRQoL in young adults from adolescence to adulthood and healthcare consultations were few.